La quantification nominale - Viviane Arigne (Corela, 2022)
This article addresses nominal quantification in English in relation to discrete and continuous quantity, the two semantic categories of discrete and continuous / mass being analysed as interpretations of syntax. It re-examines the hypothesis of non-quantifiable continuous nouns as well as some theoretical questions such as overloaded definitions, unexploited oppositions or notions found without an explicit definition, as is sometimes the case with the concept of collective. The study then proceeds to examine semantic multiplicity in connection with grammatical number. Plural is examined in association with numerals and fuzzy quantifiers. The singular category also yields interpretations of multiplicity, whether with mass-nouns or with discrete collective nouns. This, together with the possible conversion of the latter into mass-nouns, draws one’s attention to a mode of reference shared by mass nouns and collective discrete nouns.